1981
DOI: 10.3758/bf03333616
|View full text |Cite
|
Sign up to set email alerts
|

Bizarreness and recall

Abstract: Although memory experts have long advocated the use of bizarre imagery to aid memory, most research has failed to find bizarreness to be effective. Recently, bizarreness has been shown to be effective, but those experiments involved mixed lists in which each subject had both bizarre and nonbizarre materials. The goal of the present research was to use the same materials but in an unmixed-list design in which each subject had only bizarre or only nonbizarre sentences.Contrary to previous research, there were no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
20
1
2

Year Published

1987
1987
2011
2011

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 5 publications
(9 reference statements)
0
20
1
2
Order By: Relevance
“…First, processing time may not be the best measure of attention. Although Cox and Wollen (1981) and Wollen and Cox (1981) equated processing time with attention in their explanation of the bizarreness effect, earlier models that included reference to attentional mechanisms suggested that attention could be measured in a different way. For example, Merry (1980) and Merry and Graham (1978) described attention not in terms of processing time but in terms of cognitive-resource allocation-that is, they suggested (a) that comprehension of bizarre information requires more cognitive resources (not merely more time) than does comprehension of common information and (b) that the increased effort explains the memory advantage for bizarre items relative to common items.…”
mentioning
confidence: 96%
“…First, processing time may not be the best measure of attention. Although Cox and Wollen (1981) and Wollen and Cox (1981) equated processing time with attention in their explanation of the bizarreness effect, earlier models that included reference to attentional mechanisms suggested that attention could be measured in a different way. For example, Merry (1980) and Merry and Graham (1978) described attention not in terms of processing time but in terms of cognitive-resource allocation-that is, they suggested (a) that comprehension of bizarre information requires more cognitive resources (not merely more time) than does comprehension of common information and (b) that the increased effort explains the memory advantage for bizarre items relative to common items.…”
mentioning
confidence: 96%
“…In the mixed-list condition, the retrieval set encompasses an assortment of usual and unusual items, conferring relative distinctiveness onto the unusual condition, which in turn produces the typical effect in recall. This possibility has been raised with several variables that are subject to design effects, such as generation and bizarreness (Begg et al, 1989;Cox & Wollen, 1981;McDaniel et al, 2000;McDaniel et al, 2005;Schmidt, in press). …”
mentioning
confidence: 99%
“…Another important factor in determining the bizarreness effect is list structure (mixed lists, in which both bizarre and common sentences are presented, vs. unmixed lists, in which all sentences presented are bizarre or common). The majority of studies done with unmixed lists (Collyer, Jonides, & Bevan, 1972;Cox & Wollen, 1981;Marshall, Nau, & Chandler, 1980) have not resulted in superior retention for bizarre as opposed to common items (see Einstein, McDaniel, & Lackey, 1989, for an important exception). In contrast, the majority of studies done with mixed lists (McDaniel & Einstein, 1986;O'Brien & Wolford, 1982;Pra Baldi et al, 1985) have resulted in enhanced free recall for bizarre as opposed to common items.…”
mentioning
confidence: 99%